Photocrosslinking Property of Certain Synthesized Bis(arylidene)cycloalkanone based Random Copolyesters with Computational Support and their Anticancer Study - Kiruba, B.; Chidambaravinayagam , S. (Journal of Scientific Research, 2022)
The synthesis of random copolyesters involves polycondensation of arylidene diol with curcumin and glutaryl chloride in 1:1:2 ratio. For this monomers, 2,6-bis-(4-hydroxy benzylidene) cyclohexanone, 2,6-bis-(4-hydroxy-3-methoxybenzylidene)cyclohexanone, 2,5-bis-(4-hydroxybenzylidene)cyclopentanone and 2,5-bis-(4-hydroxy-3-methoxy benzylidene)cyclopentanone were synthesized using acid catalyzed Claisen-Schmidt reaction. Qualitative solubility tests reveal that prepared copolyesters dissolve well in polar solvents. The successful formation of copolyesters was confirmed by Fourier transform-infrared spectroscopy and proton nuclear magnetic resonance spectroscopic techniques. Glass transition temperature of prepared polymers was calculated using differential scanning calorimetric analysis. Further, the prepared copolyesters were utilized as in vitro anticancer agents against breast cancer MCF7 cells. The experimental results of phototcrosslinking property of the copolyesters was compared with that of computational method by DFT calculations which shows coincidence of both.